2004
DOI: 10.1529/biophysj.104.040980
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Amyloid β Dimer Formation

Abstract: Recent experiments with amyloid beta (Abeta) peptide indicate that formation of toxic oligomers may be an important contribution to the onset of Alzheimer's disease. The toxicity of Abeta oligomers depends on their structure, which is governed by assembly dynamics. Due to limitations of current experimental techniques, a detailed knowledge of oligomer structure at the atomic level is missing. We introduce a molecular dynamics approach to study Abeta dimer formation. 1), We use discrete molecular dynamics simul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
244
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(271 citation statements)
references
References 101 publications
24
244
2
1
Order By: Relevance
“…33). The DMD simulation method has been adapted successfully to model proteins (23,25,26,30) and used to study folding and aggregation of a three-helix-bundle protein (22,24), the SH3 protein (27)(28)(29), and A␤ (31,32).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…33). The DMD simulation method has been adapted successfully to model proteins (23,25,26,30) and used to study folding and aggregation of a three-helix-bundle protein (22,24), the SH3 protein (27)(28)(29), and A␤ (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…In vivo and in vitro studies suggest that the time regime of A␤ oligomerization is measured in seconds to weeks (15,21), at least 7 orders of magnitude greater than that accessible by all-atom MD. To overcome this temporal barrier and enable the study of A␤ folding and assembly, we combined an efficient discrete MD (DMD) algorithm with a coarse-grained protein model (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). This simulation approach produces oligomerization speeds Ϸ10 10 greater than those obtainable with traditional MD.…”
mentioning
confidence: 99%
“…12 Over the past several years, a wide range of theoretical techniques have also been deployed to understand the formation of soluble oligomers as well. 13 For example, Klimov and Thirumalai studied a heptapeptide sequence A␤ [16][17][18][19][20][21][22] and found oligomers composed of antiparallel beta sheets. 14 Hwang et al used a thousand dimerization simulations of the same peptide with a continuum solvent model and found that kinetics played an important role in the structure formation.…”
Section: Introductionmentioning
confidence: 99%
“…15 In apparent contrast, Urbanc et al found that dimers of beta sheet structures were not stable conformations for the whole length peptides A␤ 40 and A␤ 42 . 16 More recently, using a combination of simplified protein models and discrete molecular dynamics ͑MD͒, Urbanc et al predicted globular oligomers with a hydrophobic core and exposed N-terminal residues, besides identifying residues that are involved in the oligomer formation. 17 In a recent work, Dagmar et al used fully atomistic simulations of the monomer and observed that A␤ samples many ␤-rich conformations which might serve as precursors to oligomerization.…”
Section: Introductionmentioning
confidence: 99%
“…We describe the use of simplified protein models in conjunction with the rapid simulations methodology, discrete molecular dynamics (DMD). Despite the use of DMD in simulating polymer fluids [6,7], single homopolymers [7,8], proteins [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], protein aggregates [13,17,23,24,26], and gases and liquids [27,28], we believe it is significantly underutilized in the molecular-modeling field.…”
Section: Introductionmentioning
confidence: 99%